Differences in Teak Leaf Ecoprint Results Using the Steaming Technique on Tumblr - Wibowo, Dhea Puspita Pratama; Musdalifah, Musdalifah (Universitas Negeri Semarang, 2026)
The need for design innovation in the environmentally friendly craft industry, especially in non-textile media, has so far been minimally explored in academic literature and commercial practice. The purpose of this study is to evaluate the aesthetic and technical quality of the results of the application of ecoprint using teak leaves (Tectona grandis) on plastic tumblers through a steaming technique. This study uses an experimental method with a qualitative and quantitative descriptive approach through organoleptic tests involving 20 trained panelists with a Bachelor's degree in Fashion Design. The independent variables in this study include three classifications of teak leaf age, namely shoots, young leaves, and old leaves, to determine which provides the most optimal pigmentation results and motif sharpness. The assessment instrument includes six main indicators: motif silhouette, fiber and texture, cleanliness of fold lines, color quality, shape harmony, and harmony of pattern arrangement. The results of statistical analysis show that the highest average score is obtained in the aspect of silhouette line clarity (item 1A) of 4.85, while the aspect of evenness and color suitability (item 4C) recorded the lowest score of 1.90. The Friedman Test results show an Asymp. Sig. value of 0.000 < 0.05, which proves that there is a significant difference in quality between the three leaf classifications. The research findings reveal that teak leaf buds provide the best aesthetic quality due to the high anthocyanin concentration and the flexibility of the leaf tissue that is able to adhere perfectly to the cylindrical geometry of the tumbler. In conclusion, the integration of ecoprint on the tumbler requires a precise coating and alum mordant fixation process to overcome the absorption constraints of non-textile media, while providing economic and ecological added value to national craft products.